# Difference between Two Squares equal to Repunit

## Theorem

The sequence of differences of two squares that each make a repunit begins:

 $\ds 1^2 - 0^2$ $=$ $\ds 1$ $\ds 6^2 - 5^2$ $=$ $\ds 11$ $\ds 20^2 - 17^2$ $=$ $\ds 111$ $\ds 56^2 - 45^2$ $=$ $\ds 1111$ $\ds 56^2 - 55^2$ $=$ $\ds 111$ $\ds 156^2 - 115^2$ $=$ $\ds 11 \, 111$ $\ds 340^2 - 67^2$ $=$ $\ds 111 \, 111$ $\ds 344^2 - 65^2$ $=$ $\ds 111 \, 111$ $\ds 356^2 - 125^2$ $=$ $\ds 111 \, 111$

### Corollary 1

 $\ds 6^2 - 5^2$ $=$ $\ds 11$ $\ds 56^2 - 45^2$ $=$ $\ds 1111$ $\ds 556^2 - 445^2$ $=$ $\ds 111 \, 111$ $\ds$ $:$ $\ds$

and in general for integer $n$:

$R_{2 n} = {\underbrace {55 \ldots 56}_{\text {$n - 15$'s} } }^2 - {\underbrace {44 \ldots 45}_{\text {$n - 14$'s} } }^2$

that is:

$\ds \sum_{k \mathop = 0}^{2 n - 1} 10^k = \paren {\sum_{k \mathop = 1}^{n - 1} 5 \times 10^k + 6}^2 - \paren {\sum_{k \mathop = 1}^{n - 1} 4 \times 10^k + 5}^2$

### Corollary 2

 $\ds 6^2 - 5^2$ $=$ $\ds 11$ $\ds 56^2 - 45^2$ $=$ $\ds 1111$ $\ds 5056^2 - 5045^2$ $=$ $\ds 111 \, 111$ $\ds$ $:$ $\ds$

and in general for integer $n$:

$R_{2 n} = {\underbrace{5050 \ldots 56}_{n - 1 \ 5 \text{'s} } }^2 - {\underbrace{5050 \ldots 45}_{n - 1 \ 5 \text{'s} } }^2$

that is:

$\ds \sum_{k \mathop = 0}^{2 n - 1} 10^k = \left({\sum_{k \mathop = 1}^{n - 1} 5 \times 10^{2 k - 1} + 6}\right)^2 - \left({\sum_{k \mathop = 1}^{n - 1} 5 \times 10^{2 k - 1} - 5}\right)^2$

## Proof

Let $x^2 - y^2 = R_n$ for some $n$, where $R_n$ denotes the $n$-digit repunit.

$R_n$ has at least two distinct divisors of the same parity that multiply to $R_n$.

Then from Difference of Two Squares:

$x = \dfrac {a + b} 2$
$y = \dfrac {a - b} 2$

where:

$R_n = a b$

for all $a, b$ where:

$a b = R_n$
$a$ and $b$ are of the same parity.

Here we have that $R_n$ is odd.

So both $a$ and $b$ are always odd and therefore always of the same parity.

It remains to perform the calculations and evaluate the examples.

## Examples

### Repunit $R_1$

 $\ds 1$ $=$ $\ds 1 \times 1$ $\ds \leadsto \ \$ $\ds \frac {1 + 1} 2$ $=$ $\ds 1$ $\ds \frac {1 - 1} 2$ $=$ $\ds 0$ $\ds \leadsto \ \$ $\ds 1^2 - 0^2$ $=$ $\ds 1$

$\blacksquare$

### Repunit $R_2$

We have that $11$ is a prime.

 $\ds 11$ $=$ $\ds 1 \times 11$ $\ds \leadsto \ \$ $\ds \frac {11 + 1} 2$ $=$ $\ds 6$ $\ds \frac {11 - 1} 2$ $=$ $\ds 5$ $\ds \leadsto \ \$ $\ds 6^2 - 5^2$ $=$ $\ds 36 - 25$ $\ds$ $=$ $\ds 11$

$\blacksquare$

### Repunit $R_3$

We have that:

 $\ds 111$ $=$ $\ds 3 \times 37$ $\ds 111$ $=$ $\ds 1 \times 111$

 $\ds 111$ $=$ $\ds 111 \times 1$ $\ds \leadsto \ \$ $\ds \frac {111 + 1} 2$ $=$ $\ds 56$ $\ds \frac {111 - 1} 2$ $=$ $\ds 55$ $\ds \leadsto \ \$ $\ds$  $\ds 56^2 - 55^2$ $\ds$ $=$ $\ds 3136 - 3025$ $\ds$ $=$ $\ds 111$

 $\ds 111$ $=$ $\ds 37 \times 3$ $\ds \leadsto \ \$ $\ds \frac {37 + 3} 2$ $=$ $\ds 20$ $\ds \frac {37 - 3} 2$ $=$ $\ds 17$ $\ds \leadsto \ \$ $\ds$  $\ds 20^2 - 17^2$ $\ds$ $=$ $\ds 400 - 289$ $\ds$ $=$ $\ds 111$

$\blacksquare$

### Repunit $R_4$

We have that:

 $\ds 1111$ $=$ $\ds 101 \times 11$ $\ds 1111$ $=$ $\ds 1 \times 1111$

 $\ds 1111$ $=$ $\ds 1111 \times 1$ $\ds \leadsto \ \$ $\ds \frac {1111 + 1} 2$ $=$ $\ds 556$ $\ds \frac {1111 - 1} 2$ $=$ $\ds 555$ $\ds \leadsto \ \$ $\ds$  $\ds 556^2 - 555^2$ $\ds$ $=$ $\ds 309 \, 136 - 308 \, 025$ $\ds$ $=$ $\ds 1111$

 $\ds 1111$ $=$ $\ds 101 \times 11$ $\ds \leadsto \ \$ $\ds \frac {101 + 11} 2$ $=$ $\ds 56$ $\ds \frac {101 - 11} 2$ $=$ $\ds 45$ $\ds \leadsto \ \$ $\ds$  $\ds 56^2 - 45^2$ $\ds$ $=$ $\ds 3136 - 2025$ $\ds$ $=$ $\ds 1111$

$\blacksquare$

### Repunit $R_5$

We have that:

 $\ds 11 \, 111$ $=$ $\ds 41 \times 271$ $\ds 11 \, 111$ $=$ $\ds 1 \times 11 \, 111$

 $\ds 11 \, 111$ $=$ $\ds 11 \, 111 \times 1$ $\ds \leadsto \ \$ $\ds \frac {11 \, 111 + 1} 2$ $=$ $\ds 5556$ $\ds \frac {11 \, 111 - 1} 2$ $=$ $\ds 5555$ $\ds \leadsto \ \$ $\ds$  $\ds 5556^2 - 5555^2$ $\ds$ $=$ $\ds 30 \, 869 \, 136 - 30 \, 858 \, 025$ $\ds$ $=$ $\ds 11 \, 111$

 $\ds 11 \, 111$ $=$ $\ds 271 \times 41$ $\ds \leadsto \ \$ $\ds \frac {271 + 41} 2$ $=$ $\ds 156$ $\ds \frac {271 - 41} 2$ $=$ $\ds 115$ $\ds \leadsto \ \$ $\ds$  $\ds 156^2 - 115^2$ $\ds$ $=$ $\ds 24 \, 336 - 13 \, 225$ $\ds$ $=$ $\ds 11 \, 111$

$\blacksquare$

### Repunit $R_6$

We have that:

$111 \, 111 = 3 \times 7 \times 11 \times 13 \times 37$

So, from $\sigma_0$ of $111 \, 111$, there are $32$ divisors of $111 \, 111$, which can be grouped in $16$ pairs.

Each of these will generate a Difference between Two Squares equal to $111 \, 111$.

Hence:

 $\ds 111 \, 111$ $=$ $\ds 1 \times 111 \, 111$ $\ds$ $=$ $\ds 3 \times 37 \, 037$ $\ds$ $=$ $\ds 7 \times 15 \, 873$ $\ds$ $=$ $\ds 11 \times 10 \, 101$ $\ds$ $=$ $\ds 13 \times 8547$ $\ds$ $=$ $\ds 21 \times 5291$ $\ds$ $=$ $\ds 33 \times 3367$ $\ds$ $=$ $\ds 37 \times 3003$ $\ds$ $=$ $\ds 39 \times 2849$ $\ds$ $=$ $\ds 77 \times 1443$ $\ds$ $=$ $\ds 91 \times 1221$ $\ds$ $=$ $\ds 111 \times 1001$ $\ds$ $=$ $\ds 143 \times 777$ $\ds$ $=$ $\ds 231 \times 481$ $\ds$ $=$ $\ds 259 \times 429$ $\ds$ $=$ $\ds 273 \times 407$

 $\ds 111 \, 111$ $=$ $\ds 111 \, 111 \times 1$ $\ds \leadsto \ \$ $\ds \frac {111 \, 111 + 1} 2$ $=$ $\ds 55 \, 556$ $\ds \frac {111 \, 111 - 1} 2$ $=$ $\ds 55 \, 555$ $\ds \leadsto \ \$ $\ds$  $\ds 55 \, 556^2 - 55 \, 555^2$ $\ds$ $=$ $\ds 3 \, 086 \, 469 \, 136 - 3 \, 086 \, 358 \, 025$ $\ds$ $=$ $\ds 111 \, 111$

 $\ds 111 \, 111$ $=$ $\ds 37 \, 037 \times 3$ $\ds \leadsto \ \$ $\ds \frac {37 \, 037 + 3} 2$ $=$ $\ds 18 \, 520$ $\ds \frac {37 \, 037 - 3} 2$ $=$ $\ds 18 \, 517$ $\ds \leadsto \ \$ $\ds$  $\ds 18 \, 520^2 - 18 \, 517^2$ $\ds$ $=$ $\ds 342 \, 990 \, 400 - 342 \, 879 \, 289$ $\ds$ $=$ $\ds 111 \, 111$

 $\ds 111 \, 111$ $=$ $\ds 15 \, 873 \times 7$ $\ds \leadsto \ \$ $\ds \frac {15 \, 873 + 7} 2$ $=$ $\ds 7940$ $\ds \frac {15 \, 873 - 7} 2$ $=$ $\ds 7933$ $\ds \leadsto \ \$ $\ds$  $\ds 7940^2 - 7933^2$ $\ds$ $=$ $\ds 63 \, 043 \, 600 - 62 \, 932 \, 489$ $\ds$ $=$ $\ds 111 \, 111$

 $\ds 111 \, 111$ $=$ $\ds 10 \, 101 \times 11$ $\ds \leadsto \ \$ $\ds \frac {10 \, 101 + 11} 2$ $=$ $\ds 5056$ $\ds \frac {10 \, 101 - 11} 2$ $=$ $\ds 5045$ $\ds \leadsto \ \$ $\ds$  $\ds 5056^2 - 5045^2$ $\ds$ $=$ $\ds 25 \, 563 \, 136 - 25 \, 452 \, 025$ $\ds$ $=$ $\ds 111 \, 111$

 $\ds 111 \, 111$ $=$ $\ds 8547 \times 13$ $\ds \leadsto \ \$ $\ds \frac {8547 + 13} 2$ $=$ $\ds 4280$ $\ds \frac {8547 - 13} 2$ $=$ $\ds 4267$ $\ds \leadsto \ \$ $\ds$  $\ds 4280^2 - 4267^2$ $\ds$ $=$ $\ds 18 \, 318 \, 400 - 18 \, 207 \, 289$ $\ds$ $=$ $\ds 111 \, 111$

 $\ds 111 \, 111$ $=$ $\ds 5291 \times 21$ $\ds \leadsto \ \$ $\ds \frac {5291 + 21} 2$ $=$ $\ds 2656$ $\ds \frac {5291 - 21} 2$ $=$ $\ds 2635$ $\ds \leadsto \ \$ $\ds$  $\ds 2656^2 - 2635^2$ $\ds$ $=$ $\ds 7 \, 054 \, 336 - 6 \, 943 \, 225$ $\ds$ $=$ $\ds 111 \, 111$

 $\ds 111 \, 111$ $=$ $\ds 3367 \times 33$ $\ds \leadsto \ \$ $\ds \frac {3367 + 33} 2$ $=$ $\ds 1700$ $\ds \frac {3367 - 33} 2$ $=$ $\ds 1667$ $\ds \leadsto \ \$ $\ds$  $\ds 1700^2 - 1667^2$ $\ds$ $=$ $\ds 2 \, 890 \, 000 - 2 \, 778 \, 889$ $\ds$ $=$ $\ds 111 \, 111$

 $\ds 111 \, 111$ $=$ $\ds 3003 \times 37$ $\ds \leadsto \ \$ $\ds \frac {3003 + 37} 2$ $=$ $\ds 1520$ $\ds \frac {3003 - 37} 2$ $=$ $\ds 1483$ $\ds \leadsto \ \$ $\ds$  $\ds 1520^2 - 1483^2$ $\ds$ $=$ $\ds 2 \, 310 \, 400 - 2 \, 199 \, 289$ $\ds$ $=$ $\ds 111 \, 111$

 $\ds 111 \, 111$ $=$ $\ds 2849 \times 39$ $\ds \leadsto \ \$ $\ds \frac {2849 + 39} 2$ $=$ $\ds 1444$ $\ds \frac {2849 - 39} 2$ $=$ $\ds 1405$ $\ds \leadsto \ \$ $\ds$  $\ds 1444^2 - 1405^2$ $\ds$ $=$ $\ds 2 \, 085 \, 136 - 1 \, 974 \, 025$ $\ds$ $=$ $\ds 111 \, 111$

 $\ds 111 \, 111$ $=$ $\ds 1443 \times 77$ $\ds \leadsto \ \$ $\ds \frac {1443 + 77} 2$ $=$ $\ds 760$ $\ds \frac {1443 - 77} 2$ $=$ $\ds 683$ $\ds \leadsto \ \$ $\ds$  $\ds 760^2 - 683^2$ $\ds$ $=$ $\ds 577 \, 600 - 466 \, 489$ $\ds$ $=$ $\ds 111 \, 111$

 $\ds 111 \, 111$ $=$ $\ds 1221 \times 91$ $\ds \leadsto \ \$ $\ds \frac {1221 + 91} 2$ $=$ $\ds 656$ $\ds \frac {1221 - 91} 2$ $=$ $\ds 565$ $\ds \leadsto \ \$ $\ds$  $\ds 656^2 - 565^2$ $\ds$ $=$ $\ds 430 \, 336 - 319 \, 225$ $\ds$ $=$ $\ds 111 \, 111$

 $\ds 111 \, 111$ $=$ $\ds 1001 \times 111$ $\ds \leadsto \ \$ $\ds \frac {1001 + 111} 2$ $=$ $\ds 556$ $\ds \frac {1001 - 111} 2$ $=$ $\ds 445$ $\ds \leadsto \ \$ $\ds$  $\ds 556^2 - 445^2$ $\ds$ $=$ $\ds 309 \, 136 - 198 \, 025$ $\ds$ $=$ $\ds 111 \, 111$

 $\ds 111 \, 111$ $=$ $\ds 777 \times 143$ $\ds \leadsto \ \$ $\ds \frac {777 + 143} 2$ $=$ $\ds 460$ $\ds \frac {777 - 143} 2$ $=$ $\ds 445$ $\ds \leadsto \ \$ $\ds$  $\ds 460^2 - 317^2$ $\ds$ $=$ $\ds 211 \, 600 - 100 \, 489$ $\ds$ $=$ $\ds 111 \, 111$

 $\ds 111 \, 111$ $=$ $\ds 481 \times 231$ $\ds \leadsto \ \$ $\ds \frac {481 + 231} 2$ $=$ $\ds 356$ $\ds \frac {481 - 231} 2$ $=$ $\ds 125$ $\ds \leadsto \ \$ $\ds$  $\ds 356^2 - 125^2$ $\ds$ $=$ $\ds 126 \, 736 - 15 \, 625$ $\ds$ $=$ $\ds 111 \, 111$

 $\ds 111 \, 111$ $=$ $\ds 429 \times 259$ $\ds \leadsto \ \$ $\ds \frac {429 + 259} 2$ $=$ $\ds 344$ $\ds \frac {429 - 259} 2$ $=$ $\ds 85$ $\ds \leadsto \ \$ $\ds$  $\ds 344^2 - 85^2$ $\ds$ $=$ $\ds 118 \, 336 - 7225$ $\ds$ $=$ $\ds 111 \, 111$

 $\ds 111 \, 111$ $=$ $\ds 407 \times 273$ $\ds \leadsto \ \$ $\ds \frac {407 + 273} 2$ $=$ $\ds 340$ $\ds \frac {407 - 273} 2$ $=$ $\ds 67$ $\ds \leadsto \ \$ $\ds$  $\ds 340^2 - 67^2$ $\ds$ $=$ $\ds 115 \, 600 - 4489$ $\ds$ $=$ $\ds 111 \, 111$

$\blacksquare$

### Repunit $R_7$

We have that:

 $\ds 1 \, 111 \, 111$ $=$ $\ds 239 \times 4649$ $\ds$ $=$ $\ds 1 \times 1 \, 111 \, 111$

 $\ds 1 \, 111 \, 111$ $=$ $\ds 1 \, 111 \, 111 \times 1$ $\ds \leadsto \ \$ $\ds \frac {1 \, 111 \, 111 + 1} 2$ $=$ $\ds 555 \, 556$ $\ds \frac {1 \, 111 \, 111 - 1} 2$ $=$ $\ds 555 \, 555$ $\ds \leadsto \ \$ $\ds$  $\ds 555 \, 556^2 - 555 \, 555^2$ $\ds$ $=$ $\ds 308 \, 642 \, 469 \, 136 - 308 \, 641 \, 358 \, 025$ $\ds$ $=$ $\ds 1 \, 111 \, 111$

 $\ds 1 \, 111 \, 111$ $=$ $\ds 4649 \times 239$ $\ds \leadsto \ \$ $\ds \frac {4649 + 239} 2$ $=$ $\ds 2444$ $\ds \frac {4649 - 239} 2$ $=$ $\ds 2205$ $\ds \leadsto \ \$ $\ds$  $\ds 2444^2 - 2205^2$ $\ds$ $=$ $\ds 5 \, 973 \, 136 - 4 \, 862 \, 025$ $\ds$ $=$ $\ds 1 \, 111 \, 111$

$\blacksquare$

## Sources

Both of the above sources miss the obvious $56^2 - 55^2 = 111$.